ACEP Guidelines on Acute Nontraumatic Headache Diagnosis and Management in the Emergency Department, Commentary on Behalf of the Refractory, Inpatient, Emergency Care Section of the American Headache Society. Issue 3 (16th January 2020) - Peretz, Addie; Dujari, Shefali; Cowan, Robert; Minen, Mia
Abstract : The American College of Emergency Physicians (ACEP) published guidelines in July 2019 on the diagnosis and management of acute nontraumatic headaches in the emergency department, focusing predominantly on the diagnosis of subarachnoid hemorrhage and the role of imaging and lumbar puncture in diagnosis. The ACEP Clinical Policies document is intended to aide Emergency Physicians in their approach to patients presenting with acute headache and to improve the accuracy of diagnosis, while promoting safe patient care practices. The Clinical Policies document also highlights the need for future research into best practices to distinguish primary from secondary headaches and the efficacy and safety of current treatment options for acute headaches. The following commentary on these guidelines is intended to support and expand on these guidelines from the Headache specialists' perspective, written on behalf of the Refractory, Inpatient, Emergency Care section of the American Headache Society (AHS). The commentary have been reviewed and approved by Board of Directors of the AHS.